Sodium ion positive electrode material and method for controlling residual alkali on surface of sodium ion positive electrode material

By sintering and crushing the sodium ion positive electrode material, and using a moisture releaser to control the water absorption to generate sodium hydroxide, the problem of difficult to control the residual alkali content on the surface of the positive electrode material of sodium ion battery is solved, the material and electrical properties are improved, and the battery is extended Service life.

CN119240805APending Publication Date: 2025-01-03SHANXI HUANA COPPER ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411363547.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The residual alkali content on the surface of the positive electrode material of sodium ion battery is difficult to control, resulting in an increase in the internal resistance of the battery and a shortened service life, and absorbing water too quickly in the air affects the performance of the material.

Method used

By sintering and crushing the sodium ion positive electrode material, combining the moisture releaser to contact and release moisture in the drum, controlling the water absorption, and baking in an argon atmosphere to generate sodium hydroxide, quantitatively controlling the residual alkali content on the surface to avoid gel occurrence .

Benefits of technology

The precise control of the residual alkali content on the surface of the positive electrode material of sodium ion battery is achieved, the material and electrical performance is improved, the service life of the battery is extended, and performance problems caused by excessive water absorption are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240805A_ABST
    Figure CN119240805A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion positive electrode material and a method for controlling residual alkali on the surface of the sodium ion positive electrode material. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material comprises the following steps: sintering and crushing the sodium ion positive electrode material; the crushed materials and a moisture slow-release device are placed in a roller, the roller rotates so that the materials can make contact with the moisture slow-release device, and the moisture slow-release device releases moisture so that the materials can absorb the moisture; and sealing the material absorbing the moisture in an argon atmosphere, and baking to generate sodium hydroxide in situ. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material not only can control the water absorption capacity of the material, but also can prepare sodium hydroxide growing in situ, accurately controls the content of the residual alkali on the surface of the sodium hydroxide, and eliminates the influence of the residual alkali on the surface of sodium carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a sodium ion positive electrode material and a method for controlling residual alkali on its surface. Background Art

[0002] The positive electrode material of sodium ion battery, due to the high activity of sodium source, is easy to react with water and carbon dioxide in the air to generate surface residual alkali. The residual alkali on the surface of sodium positive electrode material will not only affect the capacity and coulomb efficiency of the material, but also cause gelation during the manufacturing process of the battery, making it impossible to coat. High surface residual alkali in the battery will increase the internal resistance of the battery, thus affecting the service life of the battery cell and the system.

[0003] In addition, by directly allowing the sodium-ion battery positive electrode material to absorb moisture in the air, the moisture on the surface of the material will rise to more than 1000 ppm in a very short period of time, which is difficult to control. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one purpose of the present invention is to provide a sodium ion positive electrode material and a method for controlling residual alkali on its surface, which can solve the technical problem that the content of residual alkali on the surface of the sodium positive electrode material in the prior art cannot be controlled.

[0005] According to the first aspect of the present invention, the method for controlling the residual alkali on the surface of the sodium ion positive electrode material of the embodiment comprises the following steps: sintering and crushing the sodium ion positive electrode material; placing the crushed material and a moisture slow releaser in a drum, rotating the drum so that the material contacts the moisture slow releaser, and the moisture slow releaser releases moisture so that the material absorbs moisture; sealing and baking the material that has absorbed moisture in an argon atmosphere to generate sodium hydroxide in situ.

[0006] According to the method for controlling the residual alkali on the surface of the sodium ion positive electrode material of the embodiment of the present invention, the crushed material and the moisture releaser are placed in a drum, and the drum is rotated to make the material contact with the moisture releaser, and the moisture releaser releases moisture so that the material absorbs moisture, which is conducive to realizing accurate control of the moisture in the material, and then the material that has absorbed moisture is sealed and baked in an argon atmosphere to generate sodium hydroxide in situ, which is conducive to quantitative control of the content of generated NaOH. In addition, it has been found through research that the cause of gelation in the slurry process of sodium ion batteries is the residual alkali on the surface of the material particles; therefore, the method for controlling the residual alkali on the surface of the sodium ion positive electrode material of the embodiment of the present invention is conducive to quantitative simulation of the residual alkali on the surface of the sodium ion battery positive electrode material, so that the influence of the residual alkali on the physical and chemical properties and electrical properties of the material can be quantified, guiding the preparation of materials, and improving the gelation problem of the battery cell end during the slurry process.

[0007] Optionally, the conditions for baking the sealed material include: baking at 60° C. and baking for 72 hours to 240 hours.

[0008] Optionally, the step of sealing the material includes: sampling the material that has absorbed moisture under a dew point environment of -30°C, putting the sample into a glove box, and sealing the sample with an aluminum foil ziplock bag under an argon atmosphere.

[0009] Optionally, the method for controlling residual alkali on the surface of the sodium ion positive electrode material further includes the following step: sintering the material for in-situ generation of sodium hydroxide in a carbon dioxide atmosphere to in-situ generate sodium carbonate.

[0010] Optionally, the conditions for sintering the material of in-situ generated sodium hydroxide in a carbon dioxide atmosphere include: in a carbon dioxide environment, the pressure is 5Pa-80Pa, the insulation temperature is set at 300°C-600°C, and the insulation time is 3h-60h.

[0011] Optionally, the step of sintering and crushing the sodium ion positive electrode material includes: sintering the sodium ion positive electrode material at a high temperature of 800°C-900°C in an atmosphere furnace in a -30°C dew point environment, introducing nitrogen into the atmosphere furnace during the sintering process, and maintaining the pressure in the atmosphere furnace at 5Pa-80Pa, sintering at a constant temperature for 6h-20h, and maintaining a positive pressure environment of 5Pa-80Pa in the furnace during the heating, constant temperature and cooling stages; transferring the sintered material to a glove box filled with argon, wherein the water and oxygen concentrations in the glove box are both lower than 0.01ppm, crushing the material in the glove box, and packaging the material in the glove box.

[0012] Optionally, the sodium ion positive electrode material is a layered transition metal oxide sodium ion battery positive electrode material, the general formula of which is Na a Cu x Fe y Mn z A 1-x-y-z O2, wherein A is an element doped to replace the transition metal, and A is one or more of Li, Ni, Mg, Zn, Co, Al, Zr, and Ti, wherein 0.5<a≤1.1, 0<x≤0.5, 0<y≤0.5, and 0<z≤0.5; the values ​​of a, x, y, and z satisfy the charge balance of the chemical formula.

[0013] Optionally, the rotation speed of the drum is 5rpm-60rpm, and the rolling time is 2h-6h.

[0014] Optionally, the moisture release device includes: a shell, which is cylindrical in shape, a side wall of the shell is provided with an opening, and the shell has a receiving space connected to the opening; a porous body, the porous body is installed in the receiving space, the porous body is used to store moisture, and the moisture in the porous body is released through the opening.

[0015] The sodium ion positive electrode material according to the second aspect of the present invention includes a positive electrode material prepared by any of the above-mentioned methods for controlling the surface residual alkali of the sodium ion positive electrode material.

[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 is a flow chart of a method for controlling residual alkali on the surface of a sodium ion positive electrode material according to one embodiment of the present invention;

[0019] Figure 2 is a schematic structural diagram of a moisture slow release device according to an embodiment of the present invention;

[0020] Figure 3 is a schematic structural diagram of a drum according to an embodiment of the present invention;

[0021] Figure 4 Schematic diagram of a drum rotating on a horizontal pot mill according to an embodiment of the present invention.

[0022] Figure Number:

[0023] Moisture slow release device 10;

[0024] Shell 11; opening 111; housing 112; open end 113; top cover 114;

[0025] Porous body 12; winding core 121; porous diaphragm 122;

[0026] Roller 20;

[0027] Horizontal pot mill 30. DETAILED DESCRIPTION

[0028] Reference below Figures 1 to 4 A method for controlling the residual alkali on the surface of a sodium ion positive electrode material according to an embodiment of the present invention is described.

[0029] The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to an embodiment of the present invention comprises the following steps:

[0030] Sintering and crushing the sodium ion positive electrode material;

[0031] The crushed material and the moisture slow release device 10 are placed in the drum 20, and the drum 20 is rotated so that the material and the moisture slow release device 10 are in contact, and the moisture slow release device 10 releases moisture so that the material absorbs moisture;

[0032] The material that has absorbed moisture is sealed in an argon atmosphere and then baked to generate sodium hydroxide in situ.

[0033] In other words, the method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to the embodiment of the present invention can realize the control of the residual alkali content on the surface of the sodium ion positive electrode material, and the specific method may include the following steps:

[0034] First, the finished sodium ion cathode material is sintered and crushed to facilitate the subsequent control of the moisture content of the material by the moisture slow release device 10. For example, the finished sodium ion cathode material is pre-burned in a nitrogen atmosphere to allow the moisture in the material to overflow and the sodium carbonate to react into the material lattice.

[0035] Secondly, the crushed material and the water retarder 10 are placed together in the drum 20, and the drum 20 is driven to rotate, so that the material inside the drum 20 collides with the water retarder 10, and the water retarder 10 releases water in the drum 20. The rotation of the drum 20 can make the material and the water retarder 10 fully contact, and the water retarder 10 releases water so that the material absorbs water. By controlling the rotation speed and size of the drum 20, the contact degree between the water retarder 10 and the material can be controlled, and the amount of water absorbed by the material can be controlled by controlling the speed at which the water retarder 10 releases water, that is, the drum 20 and the water retarder 10 cooperate with each other to make the sodium positive electrode material absorb water in situ, and the water absorption of the material can be accurately controlled to achieve quantitative control of the moisture content of the material.

[0036] Again, the material that has absorbed moisture is sealed in an argon atmosphere and then baked to generate sodium hydroxide in situ. That is to say, sodium hydroxide is prepared by allowing the material to fully react with moisture under an argon protection environment at a high temperature. In situ-grown sodium hydroxide can be prepared, and the residual alkali content on the surface of the sodium hydroxide can be accurately controlled, and the influence of the residual alkali of sodium carbonate on the surface can be eliminated.

[0037] Therefore, according to the method for controlling the residual alkali on the surface of the sodium ion positive electrode material of the embodiment of the present invention, by placing the crushed material and the moisture slow release device 10 in the drum 20, the drum 20 is rotated to make the material contact with the moisture slow release device 10, and the moisture slow release device 10 releases moisture so that the material absorbs moisture, which is conducive to realizing accurate control of the moisture in the material, and then the material that has absorbed moisture is sealed and baked in an argon atmosphere to generate sodium hydroxide in situ, which is conducive to quantitative control of the content of generated NaOH. In addition, it has been found through research that the cause of gelation of sodium ion batteries during the slurrying process is the residual alkali on the surface of the material particles; therefore, the method for controlling the residual alkali on the surface of the sodium ion positive electrode material of the embodiment of the present invention is conducive to quantitative simulation of the residual alkali on the surface of the sodium ion battery positive electrode material, so that the influence of the residual alkali on the physical and chemical properties and electrical properties of the material can be quantified, guiding the preparation of materials, and improving the gelation of the battery cell during the slurrying process.

[0038] According to one embodiment of the present invention, the conditions for baking the sealed material include: baking at 60°C and baking for 72h-240h. For example, the material after the test is sampled under a dew point environment of -30°C, placed in a glove box, sealed with an aluminum foil ziplock bag under an argon atmosphere, and then transferred to a 60°C oven for baking for 72h-240h. In this embodiment, the material that has absorbed moisture is sealed and baked in an argon atmosphere, and the conditions for baking the sealed material include: baking at 60°C and baking for 72h-240h, such as baking for 72h, 80h, 90h, 100h, 120h, 150h, 200h, 230h or 240h, etc., which is conducive to fully reacting the material with moisture and preparing in-situ grown sodium hydroxide.

[0039] In some specific embodiments of the present invention, the step of sealing the material includes: sampling the material that has absorbed moisture under a dew point environment of -30°C, placing it in a glove box, and sealing it with an aluminum foil ziplock bag under an argon atmosphere. For example, the material after the test is completed is sampled under a dew point environment of -30°C, placed in a glove box, and sealed with an aluminum foil ziplock bag under an argon atmosphere. In this embodiment, by sampling the material that has absorbed moisture under a dew point environment of -30°C, placing it in a glove box, and sealing it with an aluminum foil ziplock bag under an argon atmosphere, the sealing effect can be improved, and the moisture and carbon dioxide in the environment can be prevented from affecting the control of the residual alkali content of sodium hydroxide on the surface of the positive electrode material of the sodium ion battery.

[0040] In addition, after sampling in the glove box, the moisture content of the material can be tested by the Mettler-Karl Fischer method, and the residual alkali of sodium hydroxide and sodium carbonate on the surface of the material can be tested by titration, which is helpful to accurately obtain the residual alkali content on the surface of the sodium ion positive electrode material.

[0041] According to one embodiment of the present invention, the method for controlling the residual alkali on the surface of the sodium ion positive electrode material also includes the following steps: sintering the material that generates sodium hydroxide in situ under a carbon dioxide atmosphere to generate sodium carbonate in situ. For example, by sintering the material with a high NaOH content at a low temperature under a high-purity carbon dioxide environment, the in-situ generation of sodium carbonate is achieved. In other words, a material with a high sodium hydroxide residual alkali content can be used and sintered under a high-purity carbon dioxide atmosphere to convert the residual alkali hydroxide on the surface of the material into residual alkali sodium carbonate, and eliminate the influence of the residual alkali sodium hydroxide, which is conducive to quantitatively controlling the content of generated sodium carbonate.

[0042] In some specific embodiments of the present invention, the conditions for sintering the material of in-situ generated sodium hydroxide in a carbon dioxide atmosphere include: in a carbon dioxide environment, the pressure is 5Pa-80Pa, the insulation temperature is set at 300℃-600℃, and the insulation time is 3h-60h. For example, under a dew point environment of -30℃, a high-moisture material of in-situ generated sodium hydroxide is loaded into a 330mm*330mm sagger, the loading amount is 3kg-7kg, the sagger containing the material is loaded into an atmosphere furnace, 99.9999% pure carbon dioxide is introduced into the atmosphere furnace, the pressure in the furnace is maintained at 5Pa-80Pa, the insulation temperature is set at 300℃-600℃, and the insulation time is 3h-60h. Optionally, the sintered material can be subsequently transferred to a glove box filled with argon, and the material is crushed with a small steel mill in the glove box, intermittently crushed for 5min, and then the material is sealed in an aluminum foil ziplock bag in the glove box. In this embodiment, in a carbon dioxide environment, the pressure is 5Pa-80Pa, for example, the pressure is 5Pa, 10Pa, 15Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa or 80Pa, etc.; the insulation temperature is set at 300℃-600℃, for example, the insulation temperature is 300℃, 350℃, 400℃, 450℃, 500℃ or 600℃, etc.; the insulation time is 3h-60h, for example, the insulation time is 3h, 10h, 20h, 30h, 40h, 50h or 60h, etc. The above conditions are coordinated with each other, which is beneficial to converting the residual sodium hydroxide on the surface of the material into residual sodium carbonate.

[0043] According to one embodiment of the present invention, the step of sintering and crushing the sodium ion positive electrode material includes: sintering the sodium ion positive electrode material at a high temperature of 800°C-900°C in an atmosphere furnace in a -30°C dew point environment, introducing nitrogen into the atmosphere furnace during the sintering process, and maintaining the pressure in the atmosphere furnace at 5Pa-80Pa, sintering at a constant temperature for 6h-20h, and maintaining a positive pressure environment of 5Pa-80Pa in the furnace during the heating, constant temperature and cooling stages. For example, take the prepared finished sodium ion positive electrode material, in a -30°C dew point environment, use a 330mm*330mm sagger, with a sagger capacity of 3kg-7kg, and perform high-temperature sintering at 800°C-900°C in an atmosphere furnace. During the sintering process, 99.9999% pure nitrogen is introduced into the atmosphere furnace, and the pressure in the atmosphere furnace is maintained at 5Pa-80Pa. The constant temperature sintering is carried out for 6h-20h, and the positive pressure environment in the furnace is maintained at 5Pa-80Pa in the heating, constant temperature and cooling stages. In this embodiment, the sodium ion positive electrode material is sintered at a high temperature of 800°C-900°C in an atmosphere furnace in a -30°C dew point environment, for example, the sintering temperature is 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C; during the sintering process, nitrogen is introduced into the atmosphere furnace, and the pressure in the atmosphere furnace is maintained at 5Pa-80Pa, for example, the pressure is 5Pa, 15Pa, 20Pa, 25Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa or 80Pa, etc.; constant temperature sintering for 6h-20h, for example, sintering for 6h, 10h, 12h, 15h, 16h, 18h or 20h, etc., the heating, constant temperature section and cooling section all maintain a positive pressure environment of 5Pa-80Pa in the furnace, for example, maintaining 5Pa, 15Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa or 80Pa, etc., through the above conditions, the moisture in the material can be overflowed, and the sodium carbonate reacts into the material lattice.

[0044] Optionally, the sintered material is transferred to a glove box filled with argon, the water and oxygen concentrations in the glove box are both lower than 0.01 ppm, the material is crushed in the glove box, and the material is packaged in the glove box. For example, the sintered material is transferred to a glove box filled with argon, the water and oxygen concentrations in the glove box are both lower than 0.01 ppm, the purity of argon is 99.999%, the material is crushed with a small steel mill in the glove box, the crushing is intermittent for 5 minutes, and then the material is packaged in the glove box.

[0045] In some specific embodiments of the present invention, the sodium ion positive electrode material is a layered transition metal oxide sodium ion battery positive electrode material, and the material general formula is Na a Cu x Fe y Mn z A 1-x-y-zO2, wherein A is an element doped to replace the transition metal, and A is one or more of Li, Ni, Mg, Zn, Co, Al, Zr, and Ti, wherein 0.5<a≤1.1, 0<x≤0.5, 0<y≤0.5, and 0<z≤0.5; the values ​​of a, x, y, and z satisfy the charge balance of the chemical formula. a Cu x Fe y Mn z A 1-x-y-z O2's sodium ion positive electrode material is beneficial to ensuring that the prepared sodium ion battery has good electrical properties.

[0046] According to one embodiment of the present invention, the rotation speed of the drum 20 is 5rpm-60rpm, and the rolling time is 2h-6h. For example, under a dew point environment of -30°C, the material encapsulated in an argon atmosphere and the moisture retarder 10 are loaded into the nylon drum 20. Optionally, the nylon drum 20 has a diameter of 130mm and a height of 600mm, and the upper cover of the drum 20 is sealed with an O-ring and a screw flange. Optionally, the nylon drum 20 containing the test material and the moisture retarder 10 is placed on a horizontal pot mill 30, and the rotation speed of the drum 20 is adjusted to 5rpm-60rpm, and the rolling time is 2h-6h, so that the material is fully in contact with the moisture retarder 10 in the drum 20, and the moisture retarder 10 slowly releases moisture so that the material absorbs moisture. In this embodiment, the rotation speed of the drum 20 is 5rpm-60rpm, for example, the rotation speed of the drum 20 is 5rpm, 10rpm, 15rpm, 20rpm, 25rpm, 30rpm, 35rpm, 40rpm, 50rpm or 60rpm, etc.; the rolling time is 2h-6h, for example, the rolling time is 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or 6h, etc., which can control the contact time between the material and water and realize precise control of the water absorption of the material.

[0047] Reference below Figures 2 to 4 A moisture slow release device 10 according to an embodiment of the present invention is described.

[0048] The moisture slow-release device 10 according to the embodiment of the present invention includes: a shell 11 and a porous body 12 .

[0049] Specifically, the shell 11 is a cylindrical member, and the side wall of the shell 11 is provided with an opening 111. The shell 11 has a receiving space connected to the opening 111. The porous body 12 is installed in the receiving space. The porous body 12 is used to store moisture, and the moisture in the porous body 12 is released through the opening 111.

[0050] In other words, the moisture slow release device 10 according to the embodiment of the present invention is mainly composed of a shell 11 and a porous body 12. The shell 11 is in the shape of a cylindrical member, which is convenient for the shell 11 to rotate. A receiving space is formed in the shell 11, and an opening 111 is also provided on the side wall of the shell 11 along the wall thickness direction, and the opening 111 is connected to the receiving space. The porous body 12 is installed in the receiving space, and the porous body 12 has a porous structure and can store moisture. When the cylindrical shell 11 is rotated, the moisture stored in the porous body 12 can be released to the outside of the shell 11 through the opening 111.

[0051] When the moisture slow release device 10 in this embodiment is used, the porous body 12 can be first installed in the shell 11, and then deionized water is dripped onto the porous body 12. The moisture slow release device 10 can slowly release moisture through the opening 111, and the slowly released moisture contacts the material. In this embodiment, the moisture slow release device 10 is mainly composed of the shell 11 and the porous body 12, so that the moisture slow release device 10 can slowly release moisture.

[0052] It should be noted that the moisture slow release device 10 of the embodiment of the present invention can be applied to the preparation of positive electrode materials for sodium ion batteries, and can quantitatively control the free water content on the surface of the positive electrode materials for sodium ion batteries.

[0053] Therefore, the moisture slow release device 10 according to the embodiment of the present invention is combined with the shell 11 and the porous body 12, and the moisture of the material can be quantitatively controlled through the moisture slow release device 10. By using the moisture slow release device 10 of the embodiment of the present invention, the surface moisture of the positive electrode material of the sodium ion battery can be quantitatively simulated, the influence of moisture on the material performance can be evaluated, the air stability test of the material and the slurry stability test can be carried out, etc.

[0054] According to one embodiment of the present invention, the housing 11 includes: an outer shell 112 and a top cover 114, the outer shell 112 is a cylindrical member, one end of the outer shell 112 has an open end 113, the side wall of the outer shell 112 has an opening 111, and the top cover 114 is covered at the open end 113. For example, the outer shell 112 is a cylindrical member extending in the up-down direction, and has an open end 113 at the upper end of the outer shell 112, and the open end 113 is communicated with the receiving space.

[0055] In this embodiment, the housing 112 has an open end 113, through which the porous body 12 can be installed and removed. After the porous body 12 is installed into the receiving space through the open end 113, the open end 113 can be closed by the top cover 114, which facilitates the installation and removal of the porous body 13 without affecting the setting of the opening 111.

[0056] Optionally, at least a portion of the shell 11 may be an aluminum shell, a stainless steel shell, a plastic shell, etc. The shell 11 made of the above materials is not easy to react with water and the positive electrode material of the sodium ion battery.

[0057] In some specific embodiments of the present invention, the housing 11 further comprises a sealing member, which is disposed at the open end 113 and is respectively connected to the outer shell 112 and the top cover 114 to close the assembly gap between the outer shell 112 and the top cover 114. For example, the sealing member is an O-ring, etc. In this embodiment, the sealing effect of the open end 113 is improved by the sealing member, and the sealing member plays a sealing function, which can effectively prevent moisture from overflowing from the top cover 114 to affect the slow-release effect.

[0058] According to one embodiment of the present invention, the porous body 12 includes: a core 121 and a porous diaphragm 122, the core 121 is located in the receiving space, and the porous diaphragm 122 is coated on at least a portion of the periphery of the core 121. The core 121 may have a porous structure that can contain water, and the water can be uniformly released by coating the porous diaphragm 122. For example, the core 121 uses a high-density sponge that can store water. In this embodiment, the porous body 12 uses a combination of the core 121 and the porous diaphragm 122, which can prolong the water release time, and the water release rate can be controlled according to the pore size of the porous structure.

[0059] In some specific embodiments of the present invention, the core 121 is a sponge, which has the advantages of being easy to store water, cheap, and easy to control the shape. Optionally, a polyurethane sponge is used as the core 121, and 15-30 layers of a porous diaphragm 122 with a thickness of 12 μm are wrapped on the surface of the high-density polyurethane sponge, which is conducive to controlling the release rate of water. During operation, a balance with an accuracy of 0.0001g can be used to weigh deionized water, drip it on the polyurethane sponge through a straw, and the top cover 114 is screwed on, which is conducive to achieving accurate release of water.

[0060] Optionally, the hardness of the roll core 121 can be 20D, 30D, 40D, 50D, 60D, 70D, etc., and has a good water absorption function. For example, the hardness of a high-density sponge is 20D, 30D, 40D, 50D, 60D, 70D, etc.

[0061] According to one embodiment of the present invention, the thickness of the porous membrane 122 is 10 μm to 16 μm, for example, the thickness of the porous membrane 122 is 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm, etc., so as to control the speed of water release.

[0062] In some specific embodiments of the present invention, the porosity of the porous membrane 122 is 20% to 70%. For example, the porosity of the porous membrane 122 is 20%, 25%, 30%, 40%, 50%, 60% or 70%, etc., which is convenient for controlling the rate of water release.

[0063] According to one embodiment of the present invention, the porous diaphragm 122 is a PE diaphragm or a PP diaphragm, etc., which can be selected according to the needs and the specific positive electrode material of the sodium ion battery.

[0064] In some specific embodiments of the present invention, the porous membrane 122 is a coated membrane or an uncoated membrane. When the porous membrane 122 is a coated membrane, the life of the porous membrane 122 can be extended; when the porous membrane 122 is an uncoated membrane, the cost can be saved.

[0065] It should be noted that the porous membrane 122 can satisfy one or more of the above-mentioned conditions of thickness, porosity, material, etc., so that a diversified design of the porous membrane 122 can be achieved.

[0066] According to one embodiment of the present invention, the ratio of the diameter of the core 121 to the inner diameter of the shell 11 is 1 / 2 to 3 / 4. For example, the ratio of the diameter of the core 121 to the inner diameter of the shell 11 is 0.5, 0.55, 0.6, 0.7, 0.72 or 0.75, etc., which enables the moisture release device 10 to not only store more moisture, but also does not affect the release of moisture through the opening 111.

[0067] In some specific embodiments of the present invention, the opening 111 extends along the circumference of the housing 11. For example, the housing 11 is a cylindrical member extending upward in the vertical direction, and the opening 111 extends along a portion of the outer circumference of the housing 11. In this embodiment, the opening 111 extends along the circumference of the housing 11, so that moisture can be released through the opening 111 when the housing 11 rotates.

[0068] According to one embodiment of the present invention, the number of openings 111 is multiple, and the two openings 111 at both ends of the diameter of the shell 11 are symmetrical with respect to the central axis of the shell 11. For example, the shell 11 extends in the vertical direction, and relative to the vertically extending central axis of the shell 11, one opening 111 can be set on the left side of the central axis, and another opening 111 can be set on the right side, and the two openings 111 can be symmetrical with respect to the central axis. In this embodiment, by adopting the axisymmetric two-side design, it can be effectively ensured that the material can quickly and evenly contact the moisture slow release device 10, thereby ensuring the uniformity of the material's water absorption.

[0069] In some specific embodiments of the present invention, along the axial direction of the shell 11, the spacing between the end of the shell 11 and the adjacent opening 111 is equal to the spacing between two adjacent openings 111. For example, the shell 11 extends in the vertical direction, and the shell 11 can be virtually divided into cells of the same size in the vertical direction through a plurality of openings 111 spaced apart and distributed in the vertical direction, which is also conducive to ensuring that the material can quickly and evenly contact the moisture slow release device 10, thereby ensuring the uniformity of the material's water absorption.

[0070] Optionally, the number of openings 111 is 4, and the four openings 111 are divided into two groups, specifically a first group of openings and a second group of openings, the first group of openings includes two axially symmetrical openings 111, and the second group of openings also includes two axially symmetrical openings 111. For example, the housing 11 extends in the vertical direction, the first group of openings and the second group of openings are spaced apart and distributed in the up-down direction, the first group of openings includes an opening 111 located on the left side of the central axis and another opening 111 on the right side; similarly, the second group of openings includes an opening 111 located on the left side of the central axis and another opening 111 on the right side.

[0071] Optionally, the length of the shell 112 is between 10 mm and 100 mm, and the diameter is between 10 mm and 30 mm. For example, the length of the shell 112 is 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 80 mm or 100 mm, and the diameter is 10 mm, 12 mm, 15 mm, 18 mm, 20 mm, 25 mm or 30 mm, etc., and it can be in contact with sodium ion positive electrode materials of various contents and sizes, so that it can be suitable for the preparation of positive electrode materials for cylindrical sodium ion batteries of various sizes.

[0072] The manufacturing process of the moisture slow release device 10 according to the embodiment of the present invention will be described in detail below in conjunction with specific embodiments.

[0073] (1) A 18650 aluminum shell (i.e., shell 112) is used. Four narrow slits (i.e., openings 111) with a projection length of 5 mm and a width of 0.001 to 0.003 mm are cut on the aluminum shell round tube through a wire cutting process with an accuracy of ±0.001 mm. The positions of the narrow slits are at 1 / 3 and 2 / 3 of the height from the bottom of the aluminum shell, and an axisymmetric two-side design is adopted. This ensures that the material can quickly and evenly contact the moisture release device 10, thereby ensuring the uniformity of the water absorption of the material.

[0074] (2) A polyurethane sponge is used as the core 121. The ratio of the diameter of the core 121 to the inner diameter of the shell 112 is between 1 / 2 and 3 / 4. The diameter of the core 121 is related to the amount of water added. The deionized water added to the moisture release device 10 is completely absorbed by the high-density polyurethane sponge, and no large particles of water droplets appear, which can ensure that the water is slowly released from the polyurethane sponge.

[0075] (3) Wrap 15 layers of a porous membrane 122 with a thickness of 12 μm on the surface of a high-density polyurethane sponge, place the porous membrane 122 in an aluminum shell after wire cutting, weigh a certain amount of deionized water with a 5 mL pipette, and drop it into the high-density sponge in the aluminum shell.

[0076] The present invention also provides a processing device for a positive electrode material of a sodium ion battery, comprising: a drum 20 and a moisture retarder 10, wherein the drum 20 has a mixing space, the mixing space can accommodate materials, the moisture retarder 10 is located in the mixing space, and the moisture retarder 10 is a moisture retarder 10 according to any of the above embodiments. That is, since the shell 11 is a cylindrical structure, when the drum 20 rotates, the shell 11 can also move or even rotate in the drum 20. That is, when the moisture retarder 10 and the materials are in the drum 20 together, the release of moisture and the absorption of moisture by the materials are achieved at the same time.

[0077] According to one embodiment of the present invention, the processing device for the positive electrode material of a sodium ion battery further includes a driving member, which drives the roller 20 to rotate so that the material in the mixing space absorbs the moisture released by the moisture slow release device 10.

[0078] Optionally, the driving member is a horizontal pot mill 30, and the roller 20 can be driven to rotate by the roller of the horizontal pot mill 30, which is convenient for installing and removing the roller 20 and convenient for operation. In addition, the outer circumference of the roller 20 is circular, and the surface of the roller is also circular, which is convenient for controlling the smooth rotation of the roller 20.

[0079] First, the quantitative simulation verification process of the moisture content of the sodium ion battery positive electrode material by the processing device of the sodium ion battery positive electrode material of the present invention is described in detail in combination with specific embodiments.

[0080] (1) Using a balance with an accuracy of 0.0001 g, weigh a certain amount of deionized water that has been calculated, drip it onto the high-density sponge of the water release device 10 through a 5 mL pipette, and cover it with a 18650 model top cover 114;

[0081] (2) Under a dew point environment of -30°C, the material and the water slow release device 10 are placed in a nylon drum 20. The diameter of the nylon drum 20 is 130 mm and the height is 600 mm. The upper cover of the drum 20 is sealed with an O-ring and a screw flange;

[0082] (3) Place the nylon drum 20 containing the test material and the moisture slow release device 10 on the horizontal pot mill 30, adjust the rotation speed of the drum 20 to 5 rpm-60 rpm, and roll for 2 h-6 h, so that the material is fully in contact with the moisture slow release device 10 in the drum 20, and the moisture slow release device 10 slowly releases moisture so that the material absorbs moisture;

[0083] (4) After the test, the material was sampled at a dew point of -30°C and the free water content on the surface of the material was tested using a Mettler Karl Fischer titrator.

[0084] For the convenience of comparison and explanation, comparative example 1 and comparative example and embodiment are set, wherein in comparative example 1, the moisture content of the material is directly tested; in comparative example 2, the moisture slow release device 10 is not added, and the material is milled in the nylon drum 20 for 3 hours to test the moisture content; in the embodiment, different deionized water is added through the moisture slow release device 10, and the material is milled in the nylon drum 20 for 3 hours to test the moisture content. The test results are shown in Table 1 below.

[0085] Table 1

[0086]

[0087]

[0088] It can be seen from the data in Table 1 that the free moisture content on the surface of the positive electrode material of the sodium ion battery can be quantitatively simulated by the moisture release device 10. Moreover, the free moisture content on the surface of the positive electrode material of the sodium ion battery can be quantitatively simulated to avoid the direct water absorption of the material and the uncontrollable water absorption. Moreover, by quantitatively simulating the moisture content on the surface of the material, the influence of moisture and surface residual alkali on the physical and chemical properties and electrical properties of the sodium positive electrode material can be verified. For example, by quantitatively simulating the moisture content on the surface of the material, the influence of residual alkali on the slurry performance of the positive electrode material of the sodium ion battery can be verified.

[0089] The present invention also discloses a sodium ion positive electrode material, including a positive electrode material prepared by the method for controlling the surface residual alkali of the sodium ion positive electrode material of any of the above embodiments. Since the method for controlling the surface residual alkali of the sodium ion positive electrode material according to the embodiment of the present invention is conducive to realizing quantitative simulation of the surface residual alkali of the sodium ion battery positive electrode material, the residual alkali content on the surface of the sodium ion positive electrode material of the embodiment of the present invention can be accurately controlled, which will not be described in detail here.

[0090] The present invention also discloses a sodium ion battery, which includes the sodium ion positive electrode material of any of the above embodiments. Since the control method of the surface residual alkali of the sodium ion positive electrode material according to the embodiment of the present invention is conducive to quantitative simulation of the surface residual alkali of the sodium ion battery positive electrode material, the influence of the residual alkali on the physical and chemical properties and electrical properties of the material can be quantified, which will not be described in detail here.

[0091] The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to the embodiment of the present invention is described in detail below with reference to specific embodiments.

[0092] (1) Making a water slow release device 10

[0093] First, a 18650 aluminum shell is used, and four narrow slits with a projection length of 5 mm are cut on the aluminum shell round tube through a wire cutting process with an accuracy of ±0.001 mm; a polyurethane sponge is used as a winding core 121, and 15-30 turns of a porous diaphragm 122 with a thickness of 12 μm are wrapped on the surface of the high-density polyurethane sponge.

[0094] Secondly, deionized water was weighed using a balance with an accuracy of 0.0001 g, and dripped onto the polyurethane sponge of the water release device 10 through a straw, and then the 18650-model aluminum shell cover was screwed on.

[0095] (2) Controlling the residual alkali on the surface of sodium ion positive electrode materials

[0096] S1, take the prepared NaCu 1 / 9 Fe 1 / 3 Mn 1 / 3 Ni 2 / 9 The O2 finished material is sintered at 800℃ in an atmosphere furnace in a -30℃ dew point environment using a 330mm*330mm sagger with a loading capacity of 3kg-7kg. During the sintering process, 99.9999% pure nitrogen is introduced into the atmosphere furnace, and the pressure in the atmosphere furnace is maintained at 5Pa-80Pa. The sintering is carried out at a constant temperature for 6 hours to 20 hours, and the positive pressure environment in the furnace is maintained at 5Pa-80Pa during the heating, constant temperature and cooling stages.

[0097] S2. The sintered material is transferred to a glove box filled with argon. The water and oxygen concentrations in the glove box are both lower than 0.01ppm, and the purity of argon is 99.999%. The material is crushed with a small steel mill in the glove box for 5 minutes intermittently, and then the material is packaged in the glove box.

[0098] S3. Take out the crushed material and perform Mettler Karl Fischer moisture measurement, and use the method with application number 202110377510.0 to perform titration test of sodium hydroxide and sodium carbonate on the surface of the material.

[0099] S4. In-situ generation of sodium hydroxide

[0100] S41. Under a dew point environment of -30°C, the material packaged in an argon atmosphere and the moisture slow release device 10 are placed into a nylon drum 20. The nylon drum 20 has a diameter of 130 mm and a height of 600 mm. The upper cover of the drum 20 is sealed with an O-ring and a screw flange.

[0101] S42. Place the nylon drum 20 containing the test material and the moisture retarder 10 on the horizontal pot mill 30, adjust the rotation speed of the drum 20 to 5rpm-60rpm, and roll for 2h-6h, so that the material is fully in contact with the moisture retarder 10 in the drum 20, and the moisture retarder 10 slowly releases moisture so that the material absorbs moisture.

[0102] S43. Sample the materials after the test under a dew point of -30°C, put them into a glove box, seal them with aluminum foil ziplock bags under an argon atmosphere, and then transfer them to a 60°C oven for baking for 72h-240h, i.e., the baking temperature is 60°C. Then sample them in the glove box, test the moisture content of the materials by the Mettler-Karl Fischer method, and test the residual sodium hydroxide and sodium carbonate on the surface of the materials by titration.

[0103] S5. In-situ generation of sodium carbonate:

[0104] S51, under a dew point environment of -30°C, the high sodium hydroxide residual alkali material prepared in step S4 is loaded into a 330mm*330mm sagger with a loading amount of 3kg-7kg, the sagger loaded with the material is loaded into an atmosphere furnace, 99.9999% pure carbon dioxide is introduced into the atmosphere furnace, the pressure in the furnace is maintained at 5Pa-80Pa, the insulation temperature is set at 500°C, and the insulation time is 3 hours-60 hours, that is, the secondary sintering temperature is 500°C;

[0105] S52, transferring the sintered material into a glove box filled with argon, crushing the material with a small steel mill in the glove box, intermittently crushing for 5 minutes, and then sealing the material with an aluminum foil ziplock bag in the glove box;

[0106] S53. Test the moisture content of materials by Mettler-Karl Fischer method and test the residual sodium hydroxide and sodium carbonate on the surface of materials by titration.

[0107] The material prepared in step S1 is used as the control group, and control group 1, control group 2, control group 3 and control group 4 are obtained through different experimental conditions; the material prepared in step S4 is used as the experimental group, and experimental groups 1 to 6 are obtained through different experimental conditions; the material prepared in step S5 is used as the experimental group, and experimental groups 7 and 8 are obtained through different experimental conditions. The materials of the above experimental groups and control groups are tested, and the test results shown in Table 2 below are obtained.

[0108] Table 2

[0109]

[0110]

[0111] The following is an explanation of Table 2:

[0112] (1) It can be seen from control group 2 that after baking at 800°C for 12 hours, the moisture content of the material is extremely low, and the residual alkali of NaOH reacts with the residual alkali of sodium carbonate to decompose;

[0113] (2) It can be seen from control groups 3 and 4 that the material absorbs water through the slow-release device, and the free water content of the material after absorbing water is consistent with the designed added water;

[0114] (3) It can be seen from experimental groups 1, 2, 3, 4, and 5 that by quantitatively absorbing water from the material and baking it at 60°C for 120 hours, the water is completely converted into NaOH;

[0115] (4) It can be seen from Experimental Groups 6 and 7 that by sintering the high NaOH residual alkali material in a carbon dioxide environment for 36 hours, all NaOH was converted into sodium carbonate;

[0116] (5) For the control group and the experimental group, the powder resistivity was tested using a pressure of 14 kN and a pressure of 105.5 MPa. The test results are shown in Table 3 below.

[0117] Table 3

[0118]

[0119] The following conclusions can be drawn from the above experimental and control groups:

[0120] First, by pre-burning in a nitrogen atmosphere, the water in the material is overflowed, and the sodium carbonate reacts into the material lattice. As a blank control group, the blank control group and the water release device 10 are used to make the sodium positive electrode material absorb water in situ, and the water absorption of the material can be accurately controlled;

[0121] Secondly, by making the material fully react with water at high temperature under an argon protection environment to prepare sodium hydroxide, in-situ grown sodium hydroxide can be prepared, and the residual alkali content on the surface of sodium hydroxide can be accurately controlled, and the influence of residual alkali on the surface of sodium carbonate can be eliminated;

[0122] Thirdly, a material with high sodium hydroxide residual alkali content is used for sintering in a high-purity carbon dioxide atmosphere to convert the hydroxide residual alkali on the surface of the material into sodium carbonate residual alkali and eliminate the influence of the sodium hydroxide residual alkali.

[0123] In summary, the control method of the embodiment of the present invention can quantitatively control the moisture content of the material, the content of residual sodium hydroxide on the surface and the residual sodium carbonate on the surface, avoid cross-influence, and support the research on material properties.

[0124] Other structures and operations of the sodium ion positive electrode material and the battery according to the embodiments of the present invention are known to those skilled in the art and will not be described in detail here.

[0125] In the description of the present invention, it is necessary to understand that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "inside", "outside", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0126] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0127] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0128] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for controlling the residual alkali on the surface of a sodium ion positive electrode material, characterized in that: The steps include: Sintering and crushing the sodium ion positive electrode material; The crushed material and the moisture slow release device are placed in a drum, and the drum is rotated so that the material contacts the moisture slow release device, and the moisture slow release device releases moisture so that the material absorbs moisture; The material that has absorbed moisture is sealed in an argon atmosphere and then baked to generate sodium hydroxide in situ.

2. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The conditions for baking the sealed material include: baking at 60° C. and baking for 72 hours to 240 hours.

3. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The steps to seal the material include: The material that has absorbed moisture was sampled under a dew point environment of -30°C, placed in a glove box, and sealed with an aluminum foil ziplock bag under an argon atmosphere.

4. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The following steps are also included: The material for in-situ generation of sodium hydroxide is sintered in a carbon dioxide atmosphere to generate sodium carbonate in-situ.

5. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 4, characterized in that: The conditions for sintering the material of in-situ generated sodium hydroxide in a carbon dioxide atmosphere include: in a carbon dioxide environment, the pressure is 5Pa-80Pa, the insulation temperature is set at 300°C-600°C, and the insulation time is 3h-60h.

6. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The steps of sintering and crushing the sodium ion positive electrode material include: The sodium ion positive electrode material is subjected to high-temperature sintering at 800° C.-900° C. in an atmosphere furnace in a dew point environment of -30° C., nitrogen is introduced into the atmosphere furnace during the sintering process, and the pressure in the atmosphere furnace is maintained at 5Pa-80Pa, and the constant temperature sintering is performed for 6h-20h, and the positive pressure environment in the furnace is maintained at 5Pa-80Pa in the heating, constant temperature and cooling stages; The sintered material is transferred to a glove box filled with argon gas. The water and oxygen concentrations in the glove box are both lower than 0.01 ppm. The material is crushed and packaged in the glove box.

7. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The sodium ion positive electrode material is a layered transition metal oxide sodium ion battery positive electrode material, and the material general formula is Na a Cu x Fe y Mn z A 1-x-y-z O2, wherein A is an element doped to replace the transition metal, and A is one or more of Li, Ni, Mg, Zn, Co, Al, Zr, and Ti, wherein 0.5<a≤1.1, 0<x≤0.5, 0<y≤0.5, and 0<z≤0.5; the values ​​of a, x, y, and z satisfy the charge balance of the chemical formula.

8. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The rotation speed of the drum is 5 rpm-60 rpm, and the rolling time is 2 h-6 h.

9. The method for controlling the residual alkali on the surface of the sodium ion positive electrode material according to claim 1, characterized in that: The moisture slow release device comprises: A shell, the shell is cylindrical in shape, a side wall of the shell is provided with an opening, and the shell has a receiving space in communication with the opening; A porous body is installed in the receiving space, and the porous body is used to store moisture, and the moisture in the porous body is released through the opening.

10. A sodium ion positive electrode material, characterized in that: A positive electrode material prepared by the method for controlling the surface residual alkali of a sodium ion positive electrode material according to any one of claims 1 to 9.